Prospective geriatric assessment for perioperative risk stratification in partial nephrectomy - Wunderle, Michael; Härtel, Nicolai; Wagener, Nina; Kowalewski, Karl-Friedrich; Nuhn, Philipp; Walach, Margarete; Kriegmair, Maximilian (European journal of surgical oncology, 2021)
Purpose - Comorbidities and frailty are determinants of surgical outcome. The aim of the study was to examine various measures of frailty and comorbidities in predicting postoperative outcome of partial nephrectomy (PN). - Methods - We prospectively analyzed the frailty and comorbidity status of 150 patients undergoing PN between 2015 and 2018. Primary endpoint was the occurrence of major postoperative complications (MPC) and secondary endpoints were the failure of Trifecta achievement and the need for hospital readmissions. For the transfer into clinical practice the most significant frailty parameters were summarized in a multi-dimensional test. - Results - Median age was 67 (33-93) years, 64.7% of the patients were male. Univariable regression analysis showed, that patients with increased frailty indices (Hopkins frailty score ≥2 (OR = 3.74, p = 0.005), Groningen frailty index ≥4 (OR = 2.85, p = 0.036)) are at higher risk to develop MPC. Furthermore, poor physical performance, such as a low handgrip strength or a Full-Tandem-Stand (FTS) < 10 s were associated with MPC (OR = 4.76, p = 0.014; OR = 4.48, p = 0.018) and Trifecta failure (OR = 3.60, p = 0.037, OR = 5.50, p = 0.010). Six measures were combined to the geriatric assessment in partial nephrectomy score (GAPN). A GAPN-score ≥3 proved to be a significant predictor for MPC (OR = 4.30, p = 0.029) and for Trifecta failure (OR = 0.20, p = 0.011) in multivariable regression analysis. - Conclusion - The frailty status and comorbidities are important determinants of the postoperative course after PN. These parameters should be assessed preoperatively and included in the treatment planning, especially in light of available alternative therapies. In this context, the GAPN-score may be a suitable tool.
Gesehen am 16.08.2021